Optimalisasi Fungsi Ekologi di Taman Langsat: Strategi Pengendalian Berbasis Lingkungan - Muhammad Ihsan Saladin; Arinda Yulistiyani; Diva Ceriana Pindo; Edah Jubaedah; Tri Fajar Yuliarti; Alfiya Azwa Salsadila (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Situated on 3.6 hectares in Kebayoran Baru, South Jakarta, Langsat Park operates as a vital urban lung, sequestering carbon, stabilizing the microclimate, attenuating noise pollution, and enhancing rainwater infiltration. This study aims to develop strategies to optimize the park’s ecological functions through a descriptive qualitative case study approach, encompassing direct observation, semi-structured interviews with park managers and community members, and document analysis using triangulation techniques. The findings reveal a diverse vegetation structure that supports air quality improvement and wildlife habitat, yet persistent challenges such as facility damage, vandalism, and waste accumulation disrupt the ecosystem. Proposed strategies include ecological and recreational zoning, implementation of nature-based solutions, increased community engagement via educational and conservation programs, and the reinforcement of regulations and routine maintenance. The implementation of these strategies is expected to strengthen stakeholder collaboration, sustain the park’s ecological functions as an essential urban green space, and serve as a benchmark for urban park management in the context of rapid urbanization.